Learners’ Perceptions of Marking Practices in Informal Mathematics Assessment: Evidence from Secondary Schools - Eric Machisi; Mpho Gift Manamela (Universitas Sarjanawiyata Tamansiswa, 2026)
This study examined learners’ perceptions of marking practices for informal mathematics tasks in 12 public secondary schools in the Pietersburg Circuit of the Capricorn South District, Limpopo Province, South Africa. Although previous research has extensively examined formative assessment and teacher feedback practices, limited studies have explored how learners perceive the effectiveness and usefulness of marking practices for informal mathematics tasks, particularly in under-resourced secondary school contexts. A mixed-methods survey design was employed to collect data from 125 secondary school learners across Grades 8–12. Data were gathered through an online questionnaire comprising Likert-scale and open-ended items. Quantitative data were analyzed using descriptive statistics, chi-square tests, analysis of variance, independent-samples t-tests, and Spearman correlation, while qualitative responses were analyzed thematically. The findings revealed that although self-marking was the most frequently used marking strategy in mathematics classrooms, most learners preferred teacher marking. Learners’ satisfaction with the marking system was positively associated with the frequency of teacher marking. No significant differences in perceptions of marking practices were found across grade levels, although perceptions differed significantly according to mathematics achievement level. Qualitative findings indicated that learners value consistent teacher marking, detailed explanatory feedback, supportive correction processes, and meaningful teacher involvement during feedback activities. The study concludes that while self- and peer-marking may support learner participation and self-regulation, regular teacher feedback remains central to learners’ confidence, understanding, and engagement in mathematics learning. The findings highlight the importance of balanced marking approaches and clear school-level feedback practices that support meaningful formative assessment in mathematics classrooms.